The Moderating role of databases and information systems : impact of inventory management on the operational performance of MSES - Abaling, Princess Jewel Diamond M. Gorospe, Charlene Joy C. Manayag, Genevieve D. Sagal, Mickhaela Angeleine D. 4 0 16; 5
u
Business Research: (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2